Urgensi Pendidikan Akhlak Wanita di Era 5.0 dalam Perspektif Hadis: Kajian Hadis Tematik - Wuwun Berliani; Muhammad Alif (STIKes Ibnu Sina Ajibarang, 2025)
This article was written to provide an illustration and explanation of the importance of providing moral education to a woman, because the current era has an influence on everyday life. This article discusses how and what the Prophet recommended regarding the good moral education of a woman. Then the writer arranges this writing based on the importance of this writing. Character education is very important in today's world. This is due to the many social problems in modern life. The purpose of this article is to help you understand that character education is very important in the Society 5.0 era. This research method is qualitative and based on a library research approach. The method in this research uses the kulitataip method and also uses the library method which according to the author is suitable as a method for this writing. Possible sources of information are books and scientific journals. The data analysis method used is qualitative data analysis, and this research summarizes the opinions of experts regarding character education and the Society 5.0 era. This data strengthens the author's argument when analyzing the importance of character education in the Society 5.0 era. The research results show that especially in the Society 5.0 era, it is very important to instill character education from an early age which includes religious values, nationality, independence, mutual cooperation and sincerity, and educational methods must be right on target. that it will be implemented.